Clinical performance of fixed-pressure Sphera Duo® hydrocephalus shunt - PINTO, Fernando Campos Gomes; OLIVEIRA, Matheus Fernandes de; CASTRO, João Paulo Souza de; MORAIS, João Vitor Rocha; PINTO, Flávia Morais Gomes; TEIXEIRA, Manoel Jacobsen (Arquivos de Neuro-Psiquiatria, 2020)
Introduction: Cerebral hydrodynamics complications in shunted patients are due to the malfunction of the system. The objective of this retrospective, single-center, single-arm cohort study is to confirm the safety and performance of Sphera® Duo when used in adult patients suffering from hydrocephalus, pseudotumor cerebri or arachnoid cysts. Methods: Data were generated by reviewing 112 adult patient’s charts, who were submitted to a ventriculoperitoneal shunt surgery and followed for one year after surgery. Results: The results show us that 76% of patients had their neurological symptoms improved and that the reoperation rate was 15% in the first year following surgery. Discussion: Sphera Duo® shunt system is an applicable shunt option in routine neurosurgical management of hydrocephalus by several causes. It has presented good results while mitigating effects of overdrainage. Overdrainage is especially important in adults with non-hypertensive hydrocephalus and can cause functional shunt failure, which causes subnormal ICP (particularly in the upright position) and is associated with characteristic neurological symptoms, such as postural headache and nausea. Conclusion: Sphera Duo® shunt system is safe when used in adult patients suffering from hydrocephalus, pseudotumor cerebri or arachnoid cyst.
Keywords: ventriculoperitoneal shunt; complications; reoperation; outcome